2023
DOI: 10.1038/s41598-023-31332-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the attractiveness of lips with different volumes after filling with hyaluronic acid

Abstract: To compare the attractiveness of lips with different volumes after filling in the view of laypersons, dentists, and specialists. The sample comprised close-up frontal and lateral photographs of the lips of 16 women who underwent lip filling procedure with hyaluronic acid and was divided into 2 groups. Group 1: eight women with thinner lips at pretreatment. Group 2: eight female patients with thicker lips at pretreatment. Photographs from before and 10 days after lip filling were used to assess attractiveness r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…Prior studies have demonstrated that HA-based dermal fillers are clinically effective for lip augmentation [ 1 , 7 - 10 ]. Recent technological advances have led to the development of low BDDE crosslinked HA fillers, which are expected to have an improved safety profile [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have demonstrated that HA-based dermal fillers are clinically effective for lip augmentation [ 1 , 7 - 10 ]. Recent technological advances have led to the development of low BDDE crosslinked HA fillers, which are expected to have an improved safety profile [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The labial region is not only instrumental in key functional activities such as speaking and eating, but it also significantly contributes to facial symmetry, aesthetics, and overall attractiveness [ 1 ]. Unfortunately, the lips are vulnerable to morphological changes caused by a range of factors.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past fifty years, full, plump, and pouty lips have been considered a desirable trait [6]. More and more young people undergo aesthetic surgical procedures for lip augmentation to obtain the commonly sought-after appearance [31][32][33][34]. In addition, aging creates a spectrum of undesirable changes in the lips, as for the rest of the face [11,12,35].…”
Section: Discussionmentioning
confidence: 99%
“…Asia is a large and diverse continent, and most of the readily available literature on lips focuses on Caucasian populations. 6 , 8 It is important to establish the basic foundational biophysical properties of South Asian lips and how these characteristics change with age. The objective of this study is to investigate and correlate characteristics of the vermillion skin in South Asian individuals by measuring dryness and roughness, fine lip lines, lip texture, hydration of lips, and barrier function.…”
Section: Introductionmentioning
confidence: 99%